Alpine restoration in the NSW Snowy Mountains: Interview with Roger Good - Good, R.; McDonald, Tein (Wiley-Blackwell Publishing Ltd, 2016)
© 2016 Ecological Society of Australia.With a career stretching from the 1960s, Roger Good clocked up over 50 years' experience in restoring alpine ecosystems, particularly bogs and fens. This interview (recorded not long before Roger's untimely death in 2015) shows how the evolving approaches to restoration in Australia's Snowy Mountains mirror the evolving broad discipline of restoration. Ecological Management & Restoration